Comparison of Innovative Breathable Nasal Packs With BIPP Gauze Packs in Nasal Septum Surgery - Raana Amir Akbar, Waqas Javaid, Muhammad Naeem, Mirza Muhammad Sarwar, Maryam Fatima, Hira Andleeb (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the major consequences of nasal septum surgery is bleeding so bilateral nasal packing is extensively done following nasal surgery to control this postoperative bleeding. This therapeutic blockage of nasal cavity results in discomfort associated with nasal obstruction while pack is in place. Patients also experience varying degrees of discomfort while pack is removed. Aim: To compare the outcome of using innovative breathable nasal packs with bismuth iodoform paraffin paste soaked gauze packs. Setting: Department of Otorhinolaryngology Unit II Sir Ganga Raam Hospital, Fatima Jinnah Medical University, Lahore. Duration: Six months from July 2021 to December 2021. Study design: Randomized Controlled Trial Methods: A total of 112 patients undergoing intranasal septal surgery, due to deviated nasal septum, under general anaesthesia were randomly allocated into two groups. Group A was consisted of patients who were postoperatively packed bilaterally with innovative breathable nasal packs and group B patients were packed bilaterally with conventional bismuth iodoform paraffin paste soaked gauze packs. All the packs were removed after 24 hours. Visual analogue scale was used to record outcome measures. All the information was recorded on proforma. Results: The average age of the patients was 29.60±9.18 years. Mean nasal blockage and sleep disturbance was significantly low in group A than group B [41.79±17.17 vs. 51.07 ± 22.86; p=0.017] and [51.61±14.74 vs. 61.79 ± 24.05; p=0.008]. Conclusion: Innovative breathable nasal packs are a good option for nasal packing as it causes less discomfort to the patient as compared to conventional nasal packs in terms of nasal blockage and sleep distrubance.